Export Diversification and the Structural Dynamics in the Growth Process: The Case of Pakistan (The Pakistan Development Review, 2000)
In the present paper we have tried to examine Pakistan’s experience with exports and growth by constructing several measures of diversification and structural change in Pakistan’s exports from a dis-aggregated data over a period of 27 years (1972-73 to 1997-98). Then using these measures we have tested a number of relationships among the structure of exports, export growth, aggregate growth, and world growth. By looking at the evolution and structural change of exports by sectors over the long run, we find a number of interesting results. First, the degree of export diversification increased sharply from 1979 and continued till 1985. After 1985, and with the return of the democracy in the country. There was a marked reduction in the export diversification and it went back to pre-1979 level. Secondly, a crude association of ‘traditionality’ with primary products and ‘non-traditionality’ with manufactured exports fails to represent Pakistan’s experience. As Pakistan emerged from an import substitution period into a period of structural change and free trade, its true comparative advantage was more visibly expressed, thus some manufactured exports declined while some primary products grew. Third, the shortrun dynamics of diversification and structural change show a marked pattern. Most change in the composition of exports has taken place during periods of boom in the domestic economy but when the world economy was experiencing a relatively recessionary period.